2021
DOI: 10.1017/cjn.2021.195
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Valproate Versus Dopamine Antagonists for Acute Migraine in the Emergency Department: A Systematic Review

Abstract: Background: Migraine is a common primary headache disorder diagnosed in the emergency department (ED). This systematic review sought to compare the efficacy of sodium valproate (SV) to dopamine antagonists (DA) in relieving pain due to acute migraine. Methods: Two research librarians helped create a search strategy including Embase, Ovid Medline, and the Cochrane Database of Clinical Trials from inception to June 1, 2020, updated May 19, 2021. Two investigators identified randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…58 Although sodium valproate is effective compared with placebo and is sometimes used as a rescue treatment, studies consistently show that it is no more effective than dopamine receptor antagonists such as metoclopramide and prochlorperazine. 59 Two small clinical trials have also shown benefit from the older antipsychotic medications haloperidol and chlorpromazine. 60,61 These drugs are associated with a higher risk of adverse effects, including hypotension and prolonged QT interval, and should be considered third-line treatments.…”
Section: Acute Treatment In the Emergency Department And Inpatient Se...mentioning
confidence: 99%
See 1 more Smart Citation
“…58 Although sodium valproate is effective compared with placebo and is sometimes used as a rescue treatment, studies consistently show that it is no more effective than dopamine receptor antagonists such as metoclopramide and prochlorperazine. 59 Two small clinical trials have also shown benefit from the older antipsychotic medications haloperidol and chlorpromazine. 60,61 These drugs are associated with a higher risk of adverse effects, including hypotension and prolonged QT interval, and should be considered third-line treatments.…”
Section: Acute Treatment In the Emergency Department And Inpatient Se...mentioning
confidence: 99%
“…Corticosteroids, specifically dexamethasone, were shown in a meta-analysis to reduce the likelihood of headache recurrence in the days following an emergency department visit but did not reduce acute pain better than placebo 58 . Although sodium valproate is effective compared with placebo and is sometimes used as a rescue treatment, studies consistently show that it is no more effective than dopamine receptor antagonists such as metoclopramide and prochlorperazine 59 . Two small clinical trials have also shown benefit from the older antipsychotic medications haloperidol and chlorpromazine 60,61 .…”
Section: Management Of Refractory Attacksmentioning
confidence: 99%